Instituciones y personas : la Sociedad Española de Educación Comparada 2002-2006 - Sevilla, Diego (Revista Española de Educación Comparada, 2014)
La Presidencia del Profesor Ferran Ferrer se extendió del 22.11.2002 al 08.09.2006. En estos años, la vida de la Sociedad estuvo marcada por sus grandes capacidades que le permitieron dirigirla con notable eficacia y ayudar a mejorar en todos sus miembros la docencia y la investigación en esta materia. Entre otras acciones de este período, merecen destacarse la publicación de la Revista Española de Educación Comparada también en formato electrónico, la celebración de dos Congresos Nacionales, dedicados al estudio de las Convergencias en la Educación Superior y al Derecho a la Educación en un mundo globalizado, la participación de los miembros de la Sociedad en Congresos europeos y mundiales, la calidad y fuerza comunicativa del Boletín de la SEEC, editado por Joan María Senent Sánchez y María Jesús Martínez Usarralde, y la puesta en marcha del Premio Pedro Rosselló. Professor Ferran Ferrer’s presidency lasted from the 22th of November 2002 until the 8th of August 2006. During this period, life within the society was conditioned by his great abilities, which allowed him to direct the society with remarkable efficiency and help to improve teaching and research regards all its members within this field. Among the actions undertaken during this period, especially worth of mentioning are the publication of the Spanish Journal of Comparative Education also in digital format, the celebration of two National Congresses dealing with the studying of the Convergences in Higher Education and the Right to Education in a Globalized World, the participation of the members of the Society in European and World Congresses, the quality and the communicative strength of the Spanish Society of Comparative Education Journal, which was published by Joan María Senet Sanchez and María Jesús Martínez Usarralde and the putting in operation of the Pedro Roselló price.